The Effects of a Brief Acceptance-Based Behavioral Treatment Versus Traditional Cognitive-Behavioral Treatment for Public Speaking Anxiety: An Exploratory Trial Examining Differential Effects on Performance and Neurophysiology. (September 2016) - Glassman, Lisa H.; Forman, Evan M.; Herbert, James D.; Bradley, Lauren E.; Foster, Elizabeth E.; Izzetoglu, Meltem; Ruocco, Anthony C.
Individuals with public speaking anxiety (PSA) experience fear and avoidance that can cause extreme distress, impaired speaking performance, and associated problems in psychosocial functioning. Most extant interventions for PSA emphasize anxiety reduction rather than enhancing behavioral performance. We compared the efficacy of two brief cognitive-behavioral interventions, a traditional cognitive-behavior treatment (tCBT) and an acceptance-based behavior treatment (ABBT), on public speaking performance and anxiety in a clinical sample of persons with PSA. The effects of treatment on prefrontal brain activation were also examined. Participants ( n = 21) were randomized to 90 min of an ABBT or a tCBT intervention. Assessments took place at pre- and post-treatment and included self-rated anxiety and observer-rated performance measures, a behavioral assessment, and prefrontal cortical activity measurements using functional near-infrared spectroscopy (fNIRS). Exploratory results indicated that participants in the ABBT condition experienced greater improvements in observer-rated performance relative to those in the tCBT condition, while those in the tCBT condition experienced greater reductions in subjective anxiety levels. Individuals in the ABBT condition also exhibited a trend toward greater treatment-related reductions in blood volume in the left dorsolateral prefrontal cortex relative to those who received tCBT. Overall, these findings preliminarily suggest that acceptance-based treatments may free more cognitive resources in comparison with tCBT, possibly resulting in greater improvements in objectively rated behavioral performances for ABBT interventions.